Regulatory Landscape and the Potential of Bacteriophage Applications in the United States’ Food Industry - Edwin Omar Rivera-Lopez; Natasha N. Tirko; Edward G. Dudley (Journal of Food Protection)
Bacteriophages are promising tools for mitigating bacterial contamination because of their specificity for bacterial cells. The food industry can enhance food safety and quality by applying bacteriophages in various settings, from farms to ready-to-eat (RTE) products. Renewed interest has been driven by recent advancements in research and the increasing need for sustainable alternatives in food safety. However, understanding the regulatory requirements for using bacteriophages in food and agriculture in the United States is essential. These complex and varied regulations impact the approval and implementation of bacteriophage-based solutions. Addressing these regulatory requirements is crucial to ensure that bacteriophage applications comply with safety and legal standards. This review synthesizes the evolving regulatory framework governing bacteriophage use in the United States food industry, providing a clear understanding of the evaluation and approval processes, while highlighting recent changes and addressing challenges and opportunities for effective integration into food processing.